Investasi Digital dalam Perspektif Syariah - Fata Habibullah; Akhlis Fatikhul Islam; Diva Carrisa Putri; Zhella Annisa; Rachma Indrarini (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
This study explores the dynamics of digital investment in Indonesia within the framework of Islamic economics. The rapid advancement of technology has facilitated the growth of Sharia-compliant investments through digital platforms, making investment more accessible to the Muslim population. This research categorizes several prominent types of Sharia-compliant digital investments, including Online Sharia Mutual Funds, Sharia-Compliant Stocks, UMKM Crowdfunding, Digital Gold, and Online Sharia Property. Each type is evaluated based on its adherence to Islamic principles, legal regulations, and associated risks and opportunities. The study finds that while digital investment platforms offer considerable accessibility and inclusivity, ensuring Sharia compliance remains a challenge amid evolving regulations and technological innovations. Furthermore, the study addresses the regulatory frameworks that oversee these investment types, such as POJK regulations and MUI fatwas, which play a crucial role in maintaining compliance. This research contributes to the ongoing development of Islamic digital finance in Indonesia, providing insights for regulators, platform providers, and investors who seek to expand Sharia-compliant digital investments responsibly.